Lifestyle And Reproductive Health - García-Hjarles, Marco Antonio (2015)
The aim of this paper is to demonstrate the effects of multiple lifestyles on reproductive health of men and women. Factors to consider include the following: 1) age, 2) drug use, 3) diet and weight, 4) some prescription drugs, 5) Stress and 6) environmental contamination. The old man or woman is a factor that can impair fertility, since due to study, work or other factors couples decide to postpone the offspring.Drugs such as snuff, alcohol, caffeine, marijuana, cocaine or opioids and anabolic impair fertility of the couple, essentially lowering the quality of gametes, their number and motility in the case of the male, and blocking ovulation , the largest number of abortions or longer to get pregnant in the case of women.